2002
DOI: 10.1177/107602960200800211
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Lipemia is Associated With Platelet and Monocyte Activation and Increased Monocyte Cytokine Expression in Normolipemic Men

Abstract: The activation of platelets and monocytes has been implicated in the development of cardiovascular diseases. We asked the question if postprandial lipemia following a fat- containing meal is associated with platelet and monocyte activation and increased platelet-monocyte interaction. Thirteen healthy, normal weight, normolipemic males, 20 to 49 years, consumed a 40% fat meal of whole foods. Blood samples were obtained at fasting and 3 1/2 and 6 hours after ingestion. Triglyceride levels increased to 48% over b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 36 publications
3
58
1
Order By: Relevance
“…A fat-rich meal did not affect the levels of circulating TNF in healthy subjects [14], nor did it increase them in subjects with T2D [15]. In contrast, increased monocyte TNF expression was found in response to mixed fat [40] and to a SFA (but not MUFA) in healthy individuals [32]. We found upregulated TNF in adipose tissue of CON in response to medium-chain SFA and in muscle of CON and adipose tissue of REL in response to MUFA.…”
Section: Discussionmentioning
confidence: 54%
“…A fat-rich meal did not affect the levels of circulating TNF in healthy subjects [14], nor did it increase them in subjects with T2D [15]. In contrast, increased monocyte TNF expression was found in response to mixed fat [40] and to a SFA (but not MUFA) in healthy individuals [32]. We found upregulated TNF in adipose tissue of CON in response to medium-chain SFA and in muscle of CON and adipose tissue of REL in response to MUFA.…”
Section: Discussionmentioning
confidence: 54%
“…Postprandial hypertriglyceridemia can induce a high inflammatory state in the circulation. The expression and concentrations of proinflammatory cytokines, such as tumor necrosis factor-␣, interleukin-1␤, and interleukin-6, are increased after a fat meal, and the increase in cytokines concentrations was related to increases in postprandial triglyceride concentrations (35,36 ). This suggests that eliminating postprandial hypertriglyceridemia may be helpful in inhibiting chronic inflammation.…”
Section: Discussionmentioning
confidence: 84%
“…We, along with others, have shown that consumption of a meal that is high in readily available carbohydrates and fat results in an increase in markers of oxidative stress and inflammation postprandially [8][9][10][11][12][13]. These changes are accentuated in obesity, diabetes and individuals with the MetS [14].…”
mentioning
confidence: 97%